Group Delay Features for Speaker Recognition - Thiruvaran, T.; Ambikairajah, E.; Epps, J. (IEEE, 2007)
Group delay is proposed as an effective means of representing spectral phase information as a feature in speaker recognition. Robustness of group delay features is difficult to achieve, since the spiky nature of the group delay masks the fine structure of the group delay. In this paper, two features based on group delay are proposed by reducing the effect of spikes with two different approaches. The first is log compression, to address the masking effects of the spikes, and the second is to use a subband based approach, where masking is restricted within certain bands containing the spikes. The purpose of this paper is to introduce different types of group delay feature extraction methods. The two features are evaluated on the cellular NIST 2001 database.
Keywords: speaker recognition; group delay